2017
DOI: 10.1063/1.5009049
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced effects in fluctuation-based measurements of single-polymer elasticity: A direct probe of the radius of gyration

Abstract: Single-molecule measurements of polymer elasticity are powerful, direct probes of both biomolecular structure and principles of polymer physics. Recent work has revealed low-force regimes in which biopolymer elasticity is understood through blob-based scaling models. However, the small tensions required to observe these regimes have the potential to create measurement biases, particularly due to the increased interactions of the polymer chain with tethering surfaces. Here, we examine one experimentally observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
4
1
0
Order By: Relevance
“…This value of the persistence length (0.5 nm), which is obtained using oscillatory measurements, matches well with equilibrium magnetic tweezer measurements in low force regime [ 37 , 38 , 40 ]. Specifically, Innes-gold et al [ 38 ] and Dittmore et al [ 37 ] measured persistence lengths of 0.55 and 0.5 nm, respectively. In addition, ensemble measurements using neutron scattering and other bulk techniques [ 18 , 41 ] report a persistence length of 0.6 nm.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This value of the persistence length (0.5 nm), which is obtained using oscillatory measurements, matches well with equilibrium magnetic tweezer measurements in low force regime [ 37 , 38 , 40 ]. Specifically, Innes-gold et al [ 38 ] and Dittmore et al [ 37 ] measured persistence lengths of 0.55 and 0.5 nm, respectively. In addition, ensemble measurements using neutron scattering and other bulk techniques [ 18 , 41 ] report a persistence length of 0.6 nm.…”
Section: Resultssupporting
confidence: 86%
“…The persistence length of 0.12 nm is again lower than the c-c bond length and raises the question on the validity of fitting the data with the WLC model. The Kuhn length of 0.24 nm coincides with the value obtained in other polar solvents like 2-propanol [ 21 ] and others [ 36 ] but is about five times lower than its measurement with magnetic tweezers [ 37 , 38 ]. It is noted that an earlier work by Oesterhelt et al [ 33 ] reported a Kuhn length of 0.7 nm in large size solvent molecule like hexadecane.…”
Section: Resultssupporting
confidence: 84%
“…The constant velocity pulling experiments yield a value persistence length(0.13 ± 0.02 nm). Persistence length of 0.64 ± 0.19 nm is consistent with lowforce equilibrium measurements performed using magnetic tweezers manipulation [17,48] and also other ensemble techniques [1,49]. Dittmore et.…”
Section: Force-extension Measurementsupporting
confidence: 86%
“…The value of Kuhn length obtained is b k = 0.24 nm which matches well with its value in 2-propanol(2l p ∼ 0.25 nm) and other organic solvents [45]. However, the Kuhn length 0.24 nm is about about five time less compared to 1.2 nm(or persistence length 0.6 nm) measured in lowforce magnetic tweezer measurements [17,48]. Note that a prior work by Oesterhelt et.al [41] chose a value of Kuhn length(0.7-0.8 nm) as measured for PEG in hexadecane, to model PEG elasticity with two-state FJC model in water.…”
Section: Force-extension Measurementsupporting
confidence: 81%
See 1 more Smart Citation